Student Concept Mastery and Scientific Literacy Profile on Redox Concepts in Senior High Schools in North Gorontalo - S. Gani, Melinda; Lukum, Astin; Pikoli, Masrid; A.R. Laliyo, Lukman; K. Salimi, Yuszda; La Kilo, Akram (International journal of technology and education research, 2025)
This study analyzed the profiles of students’ concept mastery and scientific literacy on the topic of reduction-oxidation (redox) reactions in three senior high schools in North Gorontalo, Indonesia. A descriptive qualitative approach was employed, involving written tests and interviews with 12th-grade students at SMAN 1, SMAN 3, and SMAN 6 North Gorontalo. The test instruments were designed based on the revised Bloom’s Taxonomy cognitive levels (C1–C6) and Programme for International Student Assessment (PISA) scientific literacy dimensions (context, content, competence, attitude). Results indicate that students have moderate overall concept mastery, with highest performance on lower-order cognitive skills remembering (C1) and understanding (C2) but substantially lower performance on higher-order skills such as applying (C3), analyzing (C4), evaluating (C5), and creating (C6). In terms of scientific literacy, students performed best in the content knowledge dimension, while showing weaknesses in scientific attitudes. Specifically, around 59% of students could recall basic facts (C1), but only 35% could tackle creation-based tasks (C6). Likewise, over 54% demonstrated understanding of scientific content, yet less than 47% exhibited strong scientific competencies or attitudes. These findings suggest that current teaching practices heavily emphasize rote learning of content, leading to decent factual knowledge but insufficient higher-order thinking and lack of engagement with science in real-life contexts. The study highlights the need for instructional innovations such as inquiry-based, problem-based, and context-oriented learning to strengthen students’ conceptual understanding at all cognitive levels and to foster scientific skills and attitudes.